Determinants of Learning Outcomes in Mathematics Education: Analyzing Internal and External Factors in the Society 5.0 Context - Muh Fajar Fazriansyah; Ikhsan Faturohman (AL-ISHLAH: Jurnal Pendidikan, 2025)
The emergence of Society 5.0, characterized by the integration of advanced digital technologies into all aspects of life, poses new challenges and opportunities in education. Understanding how internal and external factors affect student learning outcomes within this context is critical, particularly in mathematics education where self-regulation and technology use are essential. This study employed a sequential explanatory mixed-methods design to investigate the influence of internal (learning motivation, self-regulated learning, self-management) and external (digital learning quality, technological infrastructure, environmental support, lecturer competence) factors on learning outcomes in the Society 5.0 era. A total of 240 undergraduate mathematics education students participated in the quantitative phase, analyzed using SEM-PLS, followed by in-depth interviews with 30 students for qualitative exploration. Quantitative findings revealed that internal factors, especially learning motivation, had the strongest influence on academic performance. Among external factors, digital learning quality was the most significant. The Society 5.0 construct, while significantly associated with learning outcomes, did not moderate the relationship between internal/external factors and academic achievement. Qualitative data reinforced the central role of motivation and self-management, while also highlighting additional influences such as psychological well-being, health, and socioeconomic status. These findings underscore that internal psychological factors remain the primary drivers of student success in digitally enhanced learning environments. External support and technological infrastructure play a complementary role. The results suggest a need for holistic educational strategies that balance technological integration with student-centered development.